Circus Dramaturgy and Memory:: sparse notes from a historian who weaves antics - Rocho, Lara (Revista Brasileira de Estudos da Presença, 2025)
This article discusses possible ways of relating contemporary circus dramaturgy and memory. Starting from an expanded notion of dramaturgy, it considers circus dramaturgy within the context of democratization of knowledge beyond traditional boundaries, such as the circus canvas and traditional family structures, and the consequent opening to hybrid and collaborative creation processes. In dialogue with Cultural History, it proposes the understanding of artistic creation as a poetic record of memory. It seeks to address the creative dimension of memory rather than its monumental one. Finally, it contains sparse notes on the importance of considering the memory of creative processes themselves.